Konversi Limbah Organik Menjadi Sumber Cahaya Berkelanjutan: Pendekatan Teknologi untuk Lampu Hemat Energi - kresnadi, Muhamad Irfan; Sahara, Siti; Dwinovan, Nicholas (Jurnal Ilmiah Global Education, 2024)
In an effort to reduce environmental impact and utilize renewableresources, this research explores the conversion of organic waste into asustainable light source through a technological approach for energysaving lamps. The organic waste processing method is carried out byutilizing a fermentation process and special material synthesis to produceenvironmentally friendly light components. This study includescharacterization of the converted components as well as performance testsof the resulting lamps, including energy efficiency, light quality and servicelife. The results show great potential in converting organic waste into areliable and energy-efficient light source, and offer an innovative solutionto address the organic waste problem while promoting energysustainability.